Analysis of mechanical and micro structural property of aluminium metal matrix (LM25) composite hybrid with nano silicon carbide and nano alumina as reinforcement particles. (27th June 2019) - Aravind, V. Deepak; Gopal, P.; Viswanathan, A.
The effect of reinforcement of silicon carbide nano particle (SiCnp ) and nano alumina particle (Al2 O3 np) in base matrix composite of aluminium (LM25) alloy is studied. By using stir casting method, the hybrid aluminium matrix-based nano composites (AMNC) samples are made. The addition of nano particles in a base matrix increases the strength compared to pure LM25 aluminium alloy. The distributions of reinforcement particles are evident in the EDAX and SEM analysis. Both the density test and compression test results of AMNC samples are compared with the pure LM25 aluminium alloy. By increasing the percentage of reinforcements in matrix phase influences the increase in their mechanical properties. Aluminium matrix-based nano composites having high density, compression strength and wear resistance than pure aluminium. The above results indicates that the AMNC have excellent corrosion resistance and good fluidity but limited strength in high temperature.